Investigation of phosphate-regulatory transcription factors in wheat: TaPtf1 and TaMyb67 - Rong, Fan (2018)
Phosphorus (P) is one of the essential nutrients for plant growth; however, it is usually in low availability to plants in most soils. P deficiency/low-P in the early growth stages of wheat can cause reductions in tiller and head formation, which poses a threat to wheat productivity and global food security. Genetic variation of phosphate use efficiency (PUE) has been documented in wheat. PUE can be improved under P deficiency/low-P by P-stress-responsive adaptation mechanisms that increase P acquisition and/or utilisation. Major regulatory components involved in PUE include Pi itself, microRNAs, hormones and sugars. In addition, several transcriptional factors (TFs) appear to play crucial roles in the regulatory complexity controlling the expression of P-stress-responsive genes. A better understanding of their roles may help to achieve favourable expression patterns of downstream genes and hence potentials to develop wheat cultivars with improved PUE in future crop improvement programme. Using bioinformatic approaches, this study identified two TFs, TaPtf1 and TaMyb67, which may act as key components in PUE in wheat. Their roles in regulating PUE were investigated through molecular and transgenic approaches. Overexpression constructs for TaPtf1 and TaMyb67 were created and subsequently transformed into wheat by Agrobacterium-mediated transformation. Selected transgenic lines were studied for overexpression of these transgenes and their effects on growth-, harvest- and PUE-related plant traits in a soil-pot experiment under different P supply. The phenotypic effects of TaPtf1 in the transgenic lines were implicated to be P-stress responsive and likely associated with plant height, biomass, grain filling and P accumulation in shoots. The results appeared to be consistent with previous studies of TaPtf1 in wild-type wheat suggesting that TaPtf1 has a functional divergence from OsPtf1/ZmPtf1. On the other hand, TaMyb67 was shown to be a likely ecotypic variation of TaPhr1-B1. TaMyb67 transgenic lines gave no clear evidence of phenotypic differences, presumably due to the downstream P-stress-responsive genes regulated by TaMyb67 being unresponsive to high-P and the low level of (or no) overexpression of TaMyb67 under low-P in these lines.